Middle East and North Africa Economic Monitor April 2015 Towards a New Social Contract - Devarajan, Shantayanan (International Monetary Fund, 2015)
The economic outlook for the Middle East and North Africa (MENA) region in 2015 is slightly more favorable than in 2013-14, when the region as a whole grew at 3 percent a year. The World Bank group's latest MENA Economic Monitor projects MENA's economic growth to average 5.2 percent in 2015 driven by domestic consumption, easing political tensions crowding-in investments in Egypt and Tunisia, and full resumption of oil production in Libya. However the violent conflicts in Syria, Iraq, Gaza, Yemen and Libya with their spillovers to Lebanon and Jordan could make MENA's economic prospects bleak. The report has a special focus on the corrosive nature of the large energy subsidies in MENA. The MENA region is currently experiencing growth below potential, high unemployment, urban air pollution and congestion, and severe water scarcity that is undermining agriculture. The report shows how energy subsidies have contributed to these development challenges. Reforming these subsidies, therefore, should be one of the highest priorities of policymakers